2020
DOI: 10.1007/s11239-020-02239-9
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients diagnosed with acute venous thromboembolism in routine practice according to age and renal function: RE-COVERY DVT/PE study

Abstract: In randomized clinical trials (RCTs) of nonvitamin K antagonist oral anticoagulants (NOACs) for acute venous thromboembolism (VTE), ~ 12–13% of patients were elderly and ~ 26% had mild-to-moderate renal impairment. Observational studies are not restricted by the selection and treatment criteria of RCTs. In this ancillary analysis of the RE-COVERY DVT/PE global observational study, we aimed to describe patient characteristics, comorbidities, and anticoagulant therapy for subgroups of age (< or ≥ 75 years) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 19 The initial and maintenance doses of rivaroxaban are usually lower in elderly VTE patients, and the recommended standard rivaroxaban starting dose of 15mg twice daily for 3 weeks, followed by 20mg once daily may be too high for patients aged over 80 years. 18 , 28 Because of the age-related physiological changes, comorbidities, and concomitant medications, the anticoagulation in elderly patients is challenging and associated with an increased risk of adverse events. 15 , 17 Many clinical trials of anticoagulant therapy have excluded older patients, and it is controversial whether older patients are at higher risk for bleeding during anticoagulant therapy than are younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 The initial and maintenance doses of rivaroxaban are usually lower in elderly VTE patients, and the recommended standard rivaroxaban starting dose of 15mg twice daily for 3 weeks, followed by 20mg once daily may be too high for patients aged over 80 years. 18 , 28 Because of the age-related physiological changes, comorbidities, and concomitant medications, the anticoagulation in elderly patients is challenging and associated with an increased risk of adverse events. 15 , 17 Many clinical trials of anticoagulant therapy have excluded older patients, and it is controversial whether older patients are at higher risk for bleeding during anticoagulant therapy than are younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that renal impairment did not increase the risk of bleeding in rivaroxaban-treated patients. 28 , 35 However, clinicians are desirous of knowing the influence of renal insufficiency on the efficacy and safety of rivaroxaban in extremely old VTE patients in order to minimize the risk of hemorrhage while ensuring the optimal anticoagulation effect. In this study, we observed 12 bleeding events (10.81%) in patients with an eGFR value higher than or equal to 30mL/min/1.73m 2 , while no bleeding event was observed in patients with severe renal insufficiency (eGFR<30mL/min/1.73m 2 ).…”
Section: Discussionmentioning
confidence: 99%